Mandibular incisor extraction for management of class I malocclusion- A case report. - Md Nazmul Hasan; Naznin Sultana; Gazi Shamim Hassan; Mohammad Shamsuzzaman (Update Dental College Journal, 2014)
Extraction of premolar teeth to manage class I malocclusion is conventionally the management approach of choices. However class I malocclusion with tooth tissue discrepancy could be manage with the extraction of a lower incisor tooth with a more acceptable aesthetic outcome. This article describe a cases of class I malocclusion mange with extracting a mandibular lower incisor tooth.